Determinants of Student Decisions in Choosing A College: A Case Study - Dafina Amelia; Beby Karina Fawzea Sembiring; Doli Muhammad Jafar Dalimunthe (Journal of Educational Management Research, 2025)
Education plays a crucial role in human resource development, and students' decisions about which university to attend influence the quality of the education they receive. This study aims to analyze the impact of social media, campus reputation, academic service quality, and tuition fees on students' decisions in choosing Al-Azhar University Medan. A quantitative approach using multiple linear regression was used to analyze data from questionnaires completed by 289 respondents. The results showed that all four variables significantly influenced students' decisions. Social media and academic service quality had the most significant influence, followed by tuition fees and campus reputation. This study suggests the importance of integrating digital marketing and improving service quality to attract prospective students. This study's contribution enriches the understanding of the factors influencing student decisions, particularly at private universities. It can serve as a basis for developing more effective marketing strategies in higher education. Future research can expand the scope by considering external factors.